Pathophysiology of ascites: The importance of the intestine. A surgical contribution to the understanding of a medical problem - Gabriel E. Gondolesi; Carolina Rumbo; Leonardo Montes; Lucia Novellis; Diego Ramisch; Ariel Riquelme Henríquez; Mariana Ortega; Federico Viano; Thomas Schiano; Valeria Descalzi; Claudio Tiribelli; Mihai Oltean; et al. (Annals of Hepatology, 2024)
The understanding of the mechanisms for the development of ascites has evolved over the years, involving the liver, peritoneum, heart, and kidneys as key responsible for its formation. In this article, we review the pathophysiology of ascites formation, introducing the role of the intestine as a major responsible for ascites production through “a game changer” case.